Pragmatic Inclusion as Maintenance Agency: How Indonesian Elementary Teachers Sustain Inclusive Education without Special Education Teachers - Sarbini Sarbini; Fitri Nurlatifah Azzahra (Dinamika Ilmu, 2026)
Various challenges encountered in implementing inclusive education policies in Indonesia stem from a mismatch between the policies and available resources. This study seeks to explain how classroom teachers negotiate inclusive education in resource-constrained Indonesian elementary schools by examining their diagnostic practices, adaptive pedagogical strategies, and enactment of maintenance agency in the absence of special education teachers at the Garut Integrated Islamic Elementary School. The research method used in this study is a qualitative case study to capture the complex dynamics. For data collection, the researchers used in-depth interviews, observations, and reviewed some documents such as lesson plans and student assignments. The researchers selected three classroom teachers as participants for the sample. Each teacher had five years of experience in an inclusive school, although without formal training in special education. The data were systematically processed using NVivo 12, followed by data analysis, from data condensation, display, to conclusions. The findings show that inclusive education is sustained through maintenance agency, as teachers employ pragmatic adaptations to preserve learning under systemic constraints. This study introduces maintenance agency as a contextually grounded perspective on teacher agency and underscores the importance of strengthening institutional support for sustainable, inclusive education.